Increased affective empathy in bipolar patients during a manic episode - Bodnar, Anna (Braz J Psychiatry, 2017)
OBJECTIVE: To assess both cognitive and affective empathy in patients with bipolar disorder (BD) during an acute manic or depressive episode. METHODS: The study included 25 patients with BD (aged 35±14 years) during an acute manic episode, 25 bipolar patients (aged 41±14 years) during a depressive episode, and 25 healthy control subjects (aged 36±11 years). Cognitive and affective empathy were assessed using the Multifaceted Empathy Test. RESULTS: In both manic and depressive patients, a significant deficit in cognitive empathy was demonstrated. However, indices of affective empathy were significantly higher in the manic group than in depressed and control subjects. In the depressed patients, indices did not differ from those of healthy controls. For affective empathy, a significant positive correlation was found with intensity of manic symptoms and a negative correlation was found with intensity of depressive symptoms. No such correlations were observed with cognitive empathy. CONCLUSION: We found evidence of increased affective empathy (overempathizing) during a manic episode in bipolar patients. This phenomenon may be connected with disturbances in emotion inhibition related to anastrophic thinking and associated with increased activity of mirror neurons, all of which occur during a manic episode.